1977
DOI: 10.1121/1.381345
|View full text |Cite
|
Sign up to set email alerts
|

Bird song as music

Abstract: From two to five frequency peaks, representing sustained portions of white-throated sparrow (Zonotrichia albicollis) song, were derived using a Ubiquitous Spectrum Analyzer for each of more than 300 recorded songs from 58 different birds. After conversion to cents, a logarithmic unit, each bird’s song data were averaged and placed into three distributions: largest interval in whole song, largest interval between adjacent notes in each song, and all intervals between adjacent frequency peaks in each song. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The musical quality of bird songs has provided the impetus for many comparisons between the two sounds (e.g., Darwin, 1871; Dobson and Lemon, 1977; Catchpole and Slater, 1995; Marler, 2001; Miller, 2001; Slater, 2001; Baptista and Keister, 2005; Hartshorne, 2008; Araya-Salas, 2012). The current comparison provides evidence for shared neural responses.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The musical quality of bird songs has provided the impetus for many comparisons between the two sounds (e.g., Darwin, 1871; Dobson and Lemon, 1977; Catchpole and Slater, 1995; Marler, 2001; Miller, 2001; Slater, 2001; Baptista and Keister, 2005; Hartshorne, 2008; Araya-Salas, 2012). The current comparison provides evidence for shared neural responses.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers have asked, for example, whether birdsong and music share evolutionary precursors or functions (Darwin, 1871; Catchpole and Slater, 1995; Miller, 2001), tonal variation or rhythm (Dobson and Lemon, 1977; Slater, 2001; Baptista and Keister, 2005; Araya-Salas, 2012), or organization (Marler, 2001), and whether, like music, birdsong is creative (Marler, 2001; Hartshorne, 2008). Whether any particular species of songbird has music-like song depends on the parameter measured and the type of analysis employed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, early studies on pitch selection tended to be anecdotal, based on a small sample size, or lacking in analytical rigor. Two more recent studies specifically comparing pitch selection in bird song and human musical scales concluded that birdsong does not make preferential use of musical intervals found in commonly used Western musical scales (14,15). However, because these studies each only examined one species [the white-throated sparrow (Zonotrichia albicollis) and the nightingale wren (Microcerculus philomela), respectively], a conclusion that birdsong in general does not exhibit musical properties seems premature.…”
mentioning
confidence: 99%
“…Despite these numerous similarities, there have been fewer comparisons of birdsong structure to the structure of human music than language (Araya-Salas, 2012; Baptista et al, 2005; Dobson et al, 1977; Fitch, 2006; Gray et al, 2001; Hartshorne, 2008; Kneutgen, 1969; Marler, 2001; Slater, 2001; Taylor, 2013; Tierney et al, 2011); attempts have sometimes been met with skepticism (see for instance Benitez-Bribiesca, 2001, and responses to Gray et al, 2001). A reason for this could be that musicality is a highly subjective concept.…”
Section: Human Sounds and Bird Sounds: How Birdsong Bird Calls Lmentioning
confidence: 99%